Designing the 112 Call Centre Service System in Sidoarjo Regency using the Object-Oriented Analysis and Design (OOAD) Method - Ningrum, Dea Kusuma; Mohammad Dimas Ardiansyah; Rizky Tri Aji Setiawan; Alya Maytsa Ismawardi; Anindo Saka Fitri (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The 112 call centre in Sidoarjo district faces significant challenges, including a high number of false alarms, which account for 85% of all calls. This hampers the efficiency of the service, especially with the limited number of call takers and inefficient manual information flow. This research aims to develop a technology-based reporting system using an OOAD method (Analysis, Design, Build, Operate) approach to improve the reliability and efficiency of emergency services. The system includes E-KYC-based report verification features to filter false reports, real-time report status tracking, and integration between related parties such as the community, administration, and response units (police, ambulance, fire). The results show that the designed system is able to significantly reduce false reports, improve service response through report prioritisation, and provide community access to monitor reports independently. This approach not only overcomes operational constraints, but also provides more transparent and efficient emergency services. It is hoped that this system can become a standard model for modernising emergency services in the digital age.